2011
DOI: 10.1177/147323001103900115
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Colloid Pre-Loading on Thromboelastography Prior to Caesarean Delivery: Hydroxyethyl Starch 130/0.4 versus Succinylated Gelatine

Abstract: This prospective, randomized, double-blind study compared the effects on thromboelastography (TEG) of pre-loading with two different colloid fluids prior to spinal anaesthesia for caesarean section. Healthy full-term parturients received either 500 ml 6% hydroxyethyl starch 130/0.4 (HES, n = 25) or 500 ml 4% succinylated gelatine (GEL, n = 25) prior to spinal anaesthesia. TEG parameters including reaction time (r-time), clot formation time (k-time), clot formation rate (α-angle) and maximum amplitude (MA) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 24 publications
(22 reference statements)
0
11
0
Order By: Relevance
“…Our results also indicated that the use of HES was not associated with any increased propensity to bleeding and standard coagulation parameters were unaltered; this lack of clinically significant bleeding is likely due to the very mild coagulation impairment produced by 500 ml 6% HES (130/0.4) preloading, only detectable by thromboelastography. 23 There was no postoperative renal dysfunction in any patient, and no differences between the two groups regarding plasma creatinine variation from day 0 to day 1. This is also in accordance with recent studies showing the safety of this third-generation HES on renal function, 24 25 particularly when used in an acute trauma setting with hypovolaemic risk.…”
Section: Hesmentioning
confidence: 72%
“…Our results also indicated that the use of HES was not associated with any increased propensity to bleeding and standard coagulation parameters were unaltered; this lack of clinically significant bleeding is likely due to the very mild coagulation impairment produced by 500 ml 6% HES (130/0.4) preloading, only detectable by thromboelastography. 23 There was no postoperative renal dysfunction in any patient, and no differences between the two groups regarding plasma creatinine variation from day 0 to day 1. This is also in accordance with recent studies showing the safety of this third-generation HES on renal function, 24 25 particularly when used in an acute trauma setting with hypovolaemic risk.…”
Section: Hesmentioning
confidence: 72%
“…This is particularly important since previous studies of pregnant patients undergoing cesarean delivery receiving HES showed impairment in viscoelastic testing despite the rise in coagulation factors during pregnancy. In these patients, thromboelastometry demonstrated impairment in clot formation and clot firmness [12] and thromboelastography showed a mild hypocoagulable state [11, 13]. …”
Section: Discussionmentioning
confidence: 99%
“…Fibrinogen is vital for the development of a firm clot and achieving hemostasis. Furthermore, in healthy term patients, functional coagulation profiles measured with thromboelastography and thromboelastometry showed changes in various viscoelastic parameters with infusion of HES at the time of cesarean delivery [1113]. However, it is not known whether HES administration to patients undergoing cesarean delivery increases the risk of clinical bleeding.…”
Section: Introductionmentioning
confidence: 99%
“…About 500 -1000 ml of fluid (10-15 ml/kg crystalloid over 20 minutes) or colloid (such as 6% hydroxyethyl starch, 4% succinylated gelatin (Turker et al, 2011)) is used. Crystalloid rapidly moves into the interstitial space and therefore, the increase in central blood volume garnered from an intravenous bolus of crystalloid (no matter how much) is fleeting.…”
Section: Spinal Anesthesiamentioning
confidence: 99%